The Effect of Inflation and Profitability on Stock Returns in LQ45 Firms Registered on the Indonesian Stock Market - Rizqullah, Isti'anah; Rizki, Muhammad Irfan (Journal of Sustainable Economic and Business, 2025)
Objectives: This research intends to investigate how inflation and profitability influence the stock returns of firms listed in the LQ45 index on the Indonesia Stock Exchange (IDX). Methodology: This research employs a regression technique based on panel data utilizing the Common Effect Model (CEM) method. The information analyzed consists of secondary data obtained from 25 LQ45 firms spanning the years 2017 to 2021. To confirm the integrity of the regression model, classical assumption evaluations, including tests for multicollinearity, autocorrelation, and heteroscedasticity, were performed. Findings: The results of the analysis show that neither inflation nor profitability have a significant effect on stock returns in LQ45 companies. Although inflation has a positive coefficient, this relationship is not statistically significant. Meanwhile, profitability shows a negative relationship to stock returns, but is also not significant. This suggests that other factors outside of inflation and profitability are likely to play a greater role in determining stock returns in the Indonesian capital market. Conclusion: This study indicates that investors cannot fully rely on inflation and profitability variables as determinants of stock returns in LQ45 companies. Other factors, such as macroeconomic conditions, industry performance, and market expectations, are likely to have a greater influence in determining stock returns on the IDX.